IMPROVING THE TECHNOLOGY OF GROWING SUNFLOWER HYBRIDS BY OPTIMIZING THE NORMS OF MINERAL NUTRITION - Підтоптаний, Тарас (SWorldJournal, 2024)
The article presents the results of research obtained during the improvement of certain elements of the technology of growing sunflower hybrids in the conditions of the forest-steppe zone. The purpose of the research was to investigate the growth processe